Povidone-iodine nasal spray (Nasodine®) for the common cold: a randomized, controlled, double-blind, Phase III clinical trial - Thomas M. Polasek; Peter L. Friedland (Frontiers in Medicine)
AimTo determine the safety and efficacy of a 0.5% povidone-iodine nasal spray (Nasodine) as a treatment for the common cold (ACTRN12619000764134).MethodsA multi-center, randomized, controlled, double-blind Phase III study was conducted to assess the impact of Nasodine on the common cold. Two hundred and sixty (260) euthyroid adults with qualifying cold symptoms and meeting inclusion/exclusion criteria were randomized 2:1 to Nasodine or matching saline nasal spray (SNS), each applied 4 times daily for 5 days. Cold severity was reported using the WURSS-21 survey. The primary endpoint was impact on nasal symptoms (4-item scale), with the validated 19-item Global Severity Score (GSS) as the key secondary endpoint.ResultsAll cold severity outcomes pointed in favor of Nasodine over SNS. In the ITT (n = 260), the Nasodine benefit over SNS on nasal symptoms was 8.4% (p = 0.217). For GSS, the benefit was 12.6% (p = 0.054) in the ITT population. Post hoc subset analyses showed markedly improved benefits of Nasodine: In subjects with stronger symptoms at enrollment (ES), the GSS benefit was 17.1% (p = 0.023); for those with confirmed viral infection (VES), GSS benefit was 23.0% (p = 0.048); and for those enrolled within 24 h of symptom onset (24S), GSS benefit was 39.7% (p = 0.024). In terms of functional impairment, the Nasodine benefit was greater in all subsets, with 16.1% (p = 0.041) benefit in ITT, 22.2% in ES (p = 0.012), 32.1% in VES (p = 0.023) and 37.1% in 24S (p = 0.093). Nasodine was well tolerated, with mild transient nasopharyngeal discomfort being a common adverse effect.ConclusionNasodine treatment had a consistently positive and clinically meaningful benefit on overall cold severity when compared with saline nasal spray. Early treatment after symptom onset is an important efficacy factor.Clinical trial registrationhttps://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=377353&isReview=true, identifier ACTRN12619000764134.